Compare the estimates of the reliability function and series system under Pareto distribution - J. Sadik, Nazik; A. Rasheed, Husam; Abdul-Razzak Rasheed, Aseel (International Journal of Psychosocial Rehabilitation, 2020)
The two-parameter Pareto distribution was used to find the reliability series system, with the reliability function found for him. By comparing the estimation of distribution parameters and reliability functions using the statistical scale (MAPE) and depending on the simulation method for MLE (maximum likelihood estimation) and non-parametric estimation (empirical) methods, it was found that the MSE statistic values for the non-parametric (empirical) method were lower than the MLE method, and this indicates the advantage of the empirical method.